MANAJEMEN OBJEK WISATA PANTAI KARANG JAHE DI KABUPATEN REMBANG - Nadina, Anisa Putri; Dwimawanti, Ida Hayu (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2021)
Kabupaten Rembang is a district in Central Java Province that has a positive impact through the development of the tourism sector so as to produce Karang Jahe Beach attractions which are included in the top ten tours of interest by tourists in Central Java Province in 2018 and the following year Karang Jahe Beach experienced a decline ranking due to a decrease in the number of tourists. Karang Jahe Beach also has various problems in the function of implementing tourism object management such as cleanliness of facilities, availability of trash cans and parking spaces that are not wide. This study aims to determine how the implementation function of the management of Karang Jahe Beach tourism object in Kabupaten Rembang. This study uses descriptive qualitative research methods with observation, interviews and documentation techniques to obtain research results. The results of the study indicate that the implementation function has not run well. Problems in the implementation function, namely cleanliness in the place of business, obstacles in managing gazebo facilities, and providing uneven training to management members. The quality of tourism object management resources and budget is an inhibiting factor in the implementation of tourism object management. It is recommended that all parties involved must comply with the regulations that have been made.